The Effect of Length Fermentation Rice Straw and Tithonia (Tithonia Diversifolia) Used Local Microorganisms on The Content of Dry Matter Organic Matter and Crude Protein as Ruminant Feed. - Rahmi Elsi; Tri Astuti; Alfian Asri; Iszma Rahmayanti (Department of Agriculture, 2022)
This study aimed to examine the effect of the length of fermentation of rice straw and titania (Tithonia diversifolia) with local microorganisms (MOL) in the rumen content of cows on the content of dry matter. Organic matter. and crude protein. This study was conducted using a completely randomised design with 4 treatments and 4 replications for each treatment. The treatments consisted of PO (Combination of Rice Straw and Tithonia without MOL). Pl (Combination of Rice Straw and Tithonia with 0 Days of Fermented MOL). P2 (Combination of Rice Straw and Tithonia with 7 Days of Fermented MOL). and P3 (Combination of Rice Straw and Tithonia). With a 14-day MOL fermentation). The results of statistical analysis showed that the effect of fermenting rice straw and Tithonia (Tithonia diversifolia) with local microorganisms (MOL) in bovine rumen content had an insignificant difference (P>0.05) on the dry matter and crude protein content. but a very significant difference (P <0.01) on Organic Matter content. Based on the study's results. it can be concluded that the fermentation of rice straw and Tithonia (Tithonia diversifolia) with MOL fermentation is optimal for fermentation for 7 days.